Bactibilia in women affected with diseases of the biliary tract and pancreas. A STROBE guidelines‐adherent cross‐sectional study in Southern Italy. Issue 8 (August 2018) - Serra, Nicola; Di Carlo, Paola; Gulotta, Gaspare; d' Arpa, Francesco; Giammanco, Anna; Colomba, Claudia; Melfa, Giuseppina; Fasciana, Teresa; Sergi, Consolato
Abstract : Purpose. : Bile is a hepatobiliary lipid‐rich sterile solution, and its colonization by microorganisms defines the condition of bactibilia. In this study, we aimed to assess the bile microbiological flora and its potential link with comorbidity in women. Methodology. : We performed a microbiologic investigation on 53 female patients with biliopancreatic diseases who granted consent, and we analysed the data using a MATLAB platform. Results. : We found that the most frequent disease associated with bactibilia was pancreas head carcinoma (PHC) ( P =0.0015), while the least frequent disease was gall bladder carcinoma (GBC) ( P =0.0002). The most common microorganisms were Pseudomonas spp. ( P <0.0001) and Escherichia coli ( P <0.0001). In particular Pseudomonas spp. and E. coli were negatively correlated to PHC presence and positively correlated to CCA by both univariate and multivariate analysis. Conclusions. : Gram‐negative bacteria have been linked to a tumour‐associated inflammatory status. In the last 30 years, the analysis of mortality rate in Italy for PHC and GBC shows an increasing and a decreasing trend, respectively. Although this study targeted only 53 patients and does not reflect the frequency of diagnosis in a Southern Italian population, the decrease in GBC may raise the suggestion ofnon‐adherence to a Mediterranean diet that may have become more prevalent in Southern Italy since the 1990s.